Cell Membrane‐Camouflaged NIR II Fluorescent Ag2Te Quantum Dots‐Based Nanobioprobes for Enhanced In Vivo Homotypic Tumor Imaging. Issue 14 (24th May 2019) - Zhang, Jing‐Jing; Lin, Yi; Zhou, Hui; He, He; Ma, Jiao‐Jiao; Luo, Meng‐Yao; Zhang, Zhi‐Ling; Pang, Dai‐Wen
Abstract: The advantages of fluorescence bioimaging in the second near‐infrared (NIR II, 1000–1700 nm) window are well known; however, current NIR II fluorescent probes for in vivo tumor imaging still have many shortcomings, such as low fluorescence efficiency, unstable performance under in vivo environments, and inefficient enrichment at tumor sites. In this study, Ag2 Te quantum dots (QDs) that emit light at a wavelength of 1300 nm are assembled with poly(lactic‐ co ‐glycolic acid) and further encapsulated within cancer cell membranes to overcome the shortcomings mentioned above. The as‐prepared ≈100 nm biomimetic nanobioprobes exhibit ultrabright (≈60 times greater than that of free Ag2 Te QDs) and highly stable (≈97% maintenance after laser radiation for 1 h) fluorescence in the NIR II window. By combining the active homotypic tumor targeting capability derived from the source cell membrane with the passive enhanced permeation and retention effect, improved accumulation at tumor sites ((31 ± 2)% injection dose per gram of tumor) and a high tumor‐to‐normal tissue ratio (13.3 ± 0.7) are achieved. In summary, a new biomimetic NIR II fluorescent nanobioprobe with ultrabright and stable fluorescence, homotypic targeting and good biocompatibility for enhanced in vivo tumor imaging is developed in this study. Abstract : A superior NIR II fluorescent imaging nanobioprobe with an emission centered at 1300 nm is developed by encapsulating assembly of ultrasmall Ag2 Te quantum dots and poly(lactic‐ co ‐glycolic acid) within a cancer cell membrane. Enhanced fluorescence stability, blood circulation time, and homotypic targeting capability are achieved for in vivo tumor imaging.